1857 R.I. Rev. Stat. 204–05, ch. 80, § 2 - (:unkn) unknown (General Publisher, 1857)
Prohibited shooting ranges & galleries in the “compact part” of the city of Newport. Violators fined two hundred dollars for the first offense, and five hundred dollars for every subsequent offense.
--
Keywords: SHOOTING RANGES OR GALLERIES